Influence of shell materials on the optical performance of VO2 core–shell nanoparticle–based thermochromic films. (March 2021) - Xie, Y.M.; Zhao, X.P.; Mofid, S.A.; Tan, J.Y.; Jelle, B.P.; Yang, R.G.
Abstract: VO2 nanoparticle–based thermochromic films have shown great promise for applications in smart windows because of their relatively high luminous transmittance and solar modulation ability. To improve the lifetime of VO2 nanoparticles, environmentally stable oxide materials such as TiO2, SiO2, and ZnO have been utilized as protecting shells. However, the shell material changes the optical performance of the thermochromic films because of the variation of the dielectric environment of the VO2 nanoparticles. In this work, the effective medium theory is coupled with the transfer matrix method to study the influence of the optical constants of the shell materials and the shell thickness on the luminous transmittance and solar modulation ability of the VO2 core–shell nanoparticle–based thermochromic films. The calculation results showed that it is challenging to simultaneously improve both the luminous transmittance and the solar modulation ability of core–shell structures. With the refractive index of the shell material being between 1.6 and 2.3 (e.g. ZnO and Cr2 O3 ), there exists an optimal shell thickness to obtain the maximum solar modulation ability. The results reported in this study can be exploited to guide the design and development of high-performance VO2 core–shell nanoparticle–based thermochromic smart window films.